Pricing to market, exchange rate changes and the transmission of inflation - Fitz Gerald, John D.; Shortall, Fergal (Economic & Social Studies, 1998)
This paper examines the short-run pass through of exchange rate changes to consumer prices in Ireland. Reflecting the importance of exchange rate expectations, we develop a model of inflation where the deviation of the UK price level from its equilibrium level affects the rate of pass through of external shocks into Irish inflation. This model explains better the behaviour of the Irish rate of inflation in the 1990s and it indicates a reduction in the speed of adjustment of prices to their equilibrium after the ERM crisis.
Keywords: Exchange rates; Consumer prices; Inflation; Ireland